2023
DOI: 10.1182/blood.2022018252
|View full text |Cite
|
Sign up to set email alerts
|

In vivo HSC prime editing rescues Sickle Cell Disease in a mouse model

Abstract: Sickle Cell Disease (SCD) is a monogenic disease caused by a nucleotide mutation in the β-globin gene. Current gene therapy studies are mainly focused on lentivirus vector-mediated gene addition or CRISPR/Cas9-mediated fetal globin reactivation, leaving the root cause unfixed. We developed a vectorized prime editing system that can directly repair the SCD mutation in hematopoietic stem cells (HSCs) in vivo in a SCD mouse model (CD46/Townes mice). Our approach involved a single intravenous injection of a non-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…A complementary strategy may be to reduce the required yields by utilizing emerging methods for ex vivo HSC expansion during DP manufacturing [102,103,104 & ,105]. In the future, efforts to optimize HSC mobilization are likely to facilitate "in vivo" gene therapies by overcoming the challenges of targeting HSCs within the BM space [94,[106][107][108][109]. Presently, improvements in HSC collection are required to improve the safety, efficacy, cost, and availability of current gene therapies for SCD.…”
Section: Summary and Futurementioning
confidence: 99%
“…A complementary strategy may be to reduce the required yields by utilizing emerging methods for ex vivo HSC expansion during DP manufacturing [102,103,104 & ,105]. In the future, efforts to optimize HSC mobilization are likely to facilitate "in vivo" gene therapies by overcoming the challenges of targeting HSCs within the BM space [94,[106][107][108][109]. Presently, improvements in HSC collection are required to improve the safety, efficacy, cost, and availability of current gene therapies for SCD.…”
Section: Summary and Futurementioning
confidence: 99%
“…Notably, data disclosed in relation to the initial public offering of Prime Medicine (https://primemedicine.com) suggest that ex vivo prime editing of human CD34 + HSPCs can be quite effective and may support treatment of certain blood disorders. Indeed, a very recent study showed that human adenoviral vector-mediated delivery of prime editors to HSCs allows potent prime editing both ex vivo and in vivo, thereby providing the first proof-of-principle that prime editing of HSCs has the potential to be used as a treatment for blood disorders (Li et al, 2023). Still, progress in the field has been relatively slow, which may reflect different aspects of the technology.…”
Section: In Vivo Prime Editing Of Hscs Is On the Horizonmentioning
confidence: 99%
“…Recently, a similar approach was used by Li and coworkers to deliver the most optimized prime editing system, referred to as PE5max, to human HSCs ex vivo. By utilizing helper-dependent adenovirus (HDAd5/35++), the authors were able to achieve 3.4% prime editing of a SCD-causing HBB-variant in CD34 + HSPCs from healthy donors and 4.6% in CD34 + cells derived from SCD-patients (Li et al, 2023). Importantly, the authors were able to achieve up to 40% prime editing in vivo in HSCs in a SCD-mouse model (CD46/ Townes) by first mobilizing HSCs to the peripheral blood using G-CSF followed by a single intravenous administration of HDAd5/ 35++ vectors.…”
Section: Delivery Is the Keymentioning
confidence: 99%
See 1 more Smart Citation
“…Combining modulation of nucleotide metabolism, PEmax editors, and MMR evasion designs allows unprecedented prime editing efficiency and purity in HSPCs. Considering recent progress towards delivery of genome editors to HSCs in vivo 25,26 , these findings may help designing novel prime editing therapies to engineer quiescent HSCs in situ .…”
Section: Mainmentioning
confidence: 99%